Quantification of seedling emergence of volunteer canola and wild mustard under various burial depths - Elias Soltani; Afshin Soltani; Serollah Galesh; Farshid Ghaderi-Far; Ebrahim Zeinali (پژوهش‌های بذر ایران, 2014)
The aim of this study was to investigate and to quantify the effect of burial depth on seedling emergence of volunteer canola and wild mustard. Seeds were buried in 12 different depths (1, 2, 3, 4, 5, 6, 8, 10, 12, 15, 20, 30 cm) in 4 replications and seedling emergence was measured daily. Results indicated that emergence percentage of volunteer canola was around 98 % from 1 to 2.9 cm of burial depth and deeper depths decreased emergence percentage with a slope of -0.4 and reached to zero in burial depth of 10 cm. Seedling emergence percentage of wild mustard was described using an exponential model on the response to burial depth. According to the model, wild mustard seedling emergence decreased from 66 % in 1 cm depth to 0 % in 8 cm depth. Increasing burial depth leads to reduction of seedling emergence rate that it well quantified for both species. Seeds of these two species that buried in deeper soil layers from 10 cm for volunteer canola and 8 cm for wild mustard can expand soil seed bank and will not emerge. The results of this study may provide useful information in ecological weed management and prediction seedling emergence of weeds.